Association Between HACE1 Gene Polymorphisms and Wilms' Tumor Risk in a Chinese Population. (26th November 2017) - Jia, Wei; Deng, Zhijian; Zhu, Jinhong; Fu, Wen; Zhu, Shibo; Zhang, Li-Yu; Hu, Jinhua; Wang, Fenghua; Xia, Huimin; Liu, Guo-Chang; He, Jing
ABSTRACT: Wilms' tumor is one of the most common solid tumors of childhood; however, the genetic basis underlying the majority of cases remains largely unknown. HACE1 is a putative Wilms' tumor susceptibility gene. We investigated the association between five HACE1 gene polymorphisms and Wilms' tumor susceptibility in a Chinese population consisting of 145 patients and 531 controls. We found a significant association between HACE1 rs9404576 polymorphism and decreased Wilms' tumor risk. No significant association was detected for other polymorphisms in the overall analysis. Our results indicated that HACE1 rs9404576 polymorphism may be associated with Wilms' tumor susceptibility in the Chinese population.